Arketipe: Identifikasi Pola Dasar Persuasi Iklan - Taufik Murtono (Ornamen, 2008)
Recently, advertising is a competition arena of product and commercial company image. The increased number of product brand circulating makes the advertiser conduct every attempt to place the product image in the public reference. The archetype existence serves as the source code of human’s collective unconscious nature and as the joint well inside the brain containing the similar psychical content within human beings is utilized by the advertises as the foundation for arranging the commercial communication over the product.Keywords: Archetype, code, image.